Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.5867/medwave.2022.01.002510
|View full text |Cite
|
Sign up to set email alerts
|

Description of frequent and persistent symptoms of COVID-19 among older adults who attend senior centers

Abstract: The currently abundant bibliography on healthcare can make the search process an exhausting and frustrating experience. For this reason, it is essential to learn the basic concepts of research question formulation, information sources, and search strategies to make this process more efficient and user-friendly. The search strategy is an iterative process that allows the incorporation of tools and terms in the strategy design to optimize evidence retrieval. Each strategy varies according to the questions, the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
(28 reference statements)
1
0
0
Order By: Relevance
“…Furthermore, the most frequently reported symptoms were general fatigue, headache, fever, anosmia and/or ageusia, and cough, respectively, with no significant differences between refugees and citizens. These symptoms were also reported in many previous studies from different regions [35][36][37]. Interestingly, the results obtained in this study demonstrated that the perceptions and experiences of COVID-19 vaccination were different between refugees and citizens.…”
Section: Discussionsupporting
confidence: 84%
“…Furthermore, the most frequently reported symptoms were general fatigue, headache, fever, anosmia and/or ageusia, and cough, respectively, with no significant differences between refugees and citizens. These symptoms were also reported in many previous studies from different regions [35][36][37]. Interestingly, the results obtained in this study demonstrated that the perceptions and experiences of COVID-19 vaccination were different between refugees and citizens.…”
Section: Discussionsupporting
confidence: 84%
“…In analyzing the symptoms, it was found that the most common symptoms were headache, cough and sore throat, which is similar to what has been described in most articles [36]. These symptoms were not related to BMI.…”
Section: Discussionsupporting
confidence: 78%
“…1,2 Estos síntomas abarcan desde tos, fiebre, fatiga y disnea hasta dolor de cabeza (cefalea), dificultades cognitivas, mialgia, debilidad muscular, molestias gastrointestinales y condiciones mentales, entre otros. 3,4 Estas manifestaciones pueden perdurar tanto a corto plazo, de cuatro a doce semanas, como a largo plazo, de doce semanas a un año. [5][6][7] La fisiopatología subyacente de la disfunción pulmonar en sujetos con síntomas post COVID-19 se caracteriza por una disminución en la capacidad de difusión y una pérdida de volumen pulmonar.…”
Section: Síntomas Persistentes Y Valores Espirométricos En Post Covid...unclassified
“…Con relación a la sintomatología, se observó que el síntoma más frecuente fue el dolor de cabeza, seguido de la tos y la fatiga muscular. Estos resultados coinciden con estudios previos, como los de Contreras et al 3 y Aiyegbusi et al 17 , entre otros. 18,19 Estos hallazgos refuerzan la alta prevalencia de estos síntomas en el contexto de la COVID-19.…”
Section: Síntomas Post Covid-19unclassified